2020
DOI: 10.1039/d0cc05115b
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise reduction of interlocked viologen-based complexes in the gas phase

Abstract: Thinking outside the (blue)box: electron transfer mass spectrometry as a dual-purpose synthetic and analytical tool for supramolecular complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Interestingly, M III containing oligomers did not exhibit the same pattern, as the sulfonic groups of the porphyrins could readily bind to the central metals. It could be interesting to reduce or oxidise the metal centre incorporated in the metalloporphyrin and to observe the potential structural transformation by IMS-MS (Marshall et al, 2020).…”
Section: Structural Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, M III containing oligomers did not exhibit the same pattern, as the sulfonic groups of the porphyrins could readily bind to the central metals. It could be interesting to reduce or oxidise the metal centre incorporated in the metalloporphyrin and to observe the potential structural transformation by IMS-MS (Marshall et al, 2020).…”
Section: Structural Identificationmentioning
confidence: 99%
“…It was found that for M II containing oligomers, the charge state of the oligomer, and the corresponding number of sodium counterions, dictated if the structure formed would be “open” or “closed.” Interestingly, M III containing oligomers did not exhibit the same pattern, as the sulfonic groups of the porphyrins could readily bind to the central metals. It could be interesting to reduce or oxidise the metal centre incorporated in the metalloporphyrin and to observe the potential structural transformation by IMS-MS ( Marshall et al, 2020 ).…”
Section: Applications Of Ion Mobility Mass Spectrometry To Study Coordination Driven Self-assemblymentioning
confidence: 99%
“…Thepresent study exploits the option of electron-transfer dissociation (ETD) [28] offered by mass spectrometry (MS) platforms to selectively generate and isolate intermediate oxidation states.W hile ETD has been previously used to characterize supramolecular complexes, [29][30][31][32] we aim here to benefit from the energy-tempering properties of the buffer gas as aw ay to perform electron transfers without dissociation [33,34] and induce successive charge reductions of viologen motifs [35] embedded within [4]5NPR. Theg as-phase equilibrium geometries of the consecutive products are subsequently interrogated structurally using MS interfaced with complementary structure-sensitive techniques,that is,ion mobility [36] (IM) and infrared ion spectroscopy [37] (IRIS).…”
Section: Introductionmentioning
confidence: 99%